The pros and cons of the implementation of a chronic care model in European rural primary care: the points of view of European rural general practitioners - Donata Kurpas; Ferdinando Petrazzuoli; Katarzyna Szwamel; Jane Randall-Smith; Beata Blahova; Gindrovel Dumitra; Kateřina Javorská; András Mohos; José Simões; Victoria Tkachenko; Jean-Baptiste Kern; Carol Holland; et al. (James Cook University, 2021)
Introduction: This article describes the views of European rural general practitioners regarding the strengths, weaknesses, opportunities and threats (SWOT) of the implementation of a chronic care model (CCM) in European rural primary care. Methods: This was a mixed-methods online survey. Data were collected from 227 general practitioners between May and December 2017. Categorical data were analysed using descriptive methods while free-text responses were analysed using qualitative methods. The setting was rural primary care in nine European countries (including Central and Eastern Europe). Main outcomes measures were respondents' evaluations of a chronic care model in their rural healthcare settings in terms of SWOT. Results: The SWOT analysis showed that the expertise of healthcare professionals and the strength of relationships and communications between professionals, caregivers and patients are positive components of the CCM system. However, ensuring adequate staffing levels and staff competency are issues that would need to be addressed. Opportunities included the need to enable patients to participate in decision making by ensuring adequate health literacy. Conclusion: The CCM could certainly have benefits for health care in rural settings but staffing levels and staff competency would need to be addressed before implementation of CCM in such settings. Improving health literacy among patients and their carers will be essential to ensure their full participation in the implementation of a successful CCM.